A review of the key challenges of non-fungible tokens - Yogesh Dwivedi (Technological Forecasting and Social Change, 2023)
The nonfungible token (NFT) marketplace spiked in the recent past. The concept originated initially as a token standard of Ethereum, an open-source blockchain with smart contract functionality, where each token is characterized by distinguishable signs. These types of tokens have unique digital properties that allow their distinct identification. NFTs, with their distinct qualities, can be fluidly traded with customized values according to their ages, rarity, and liquidity. The trading of NFTs has heavily influenced the growth of the decentralized application (dApp) marketplace, as exponential returns (thousand folds from their original value) on its ever-expanding market are being observed, leading to worldwide attention. However, the NFT ecosystem is in its nascence, and the associated technologies are still in their infancy. New researchers might be fascinated with the exponential, yet nebulous evolution of NFTs; however, this novelty has contributed to the paucity of systematic and conclusive published research work on this topic. This review portrays the NFT ecosystem multidimensionally, wherein the paper commences with an overview of state-of-the-art NFT technology and furnishes summary standards and desired properties. Finally, the study concludes with an elaborate discussion of the future outlook for and prime challenges faced by NFTs.